Long‐Term Outcomes and Clinical Predictors of Mortality Following Occurrence of Stent Thrombosis - Takayuki Ishihara; Katsuki Okada; Hirota Kida; Takuya Tsujimura; Osamu Iida; Shota Okuno; Yosuke Hata; Taku Toyoshima; Naoko Higashino; Atsushi Kikuchi; Tetsuya Watanabe; Takashi Morita; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Stent thrombosis (ST) remains a significant medical issue. In particular, longer‐term mortality and clinical predictors after ST occurrence have yet to be elucidated. Methods and Results This was a multicenter, retrospective, observational study. A total of 187 definite ST cases from January 2008 to December 2017 were enrolled, and the long‐term clinical outcomes were investigated. The primary outcome measure was the cumulative mortality after ST occurrence. In addition, independent predictors of mortality were assessed. Among the stent types causing ST, bare‐metal stent, first‐generation drug‐eluting stent, second‐generation drug‐eluting stent, and third‐generation drug‐eluting stent comprised 31.0%, 19.3%, 36.9%, and 6.4% of cases, respectively. Median duration from stent implantation to ST was 680.5 (interquartile range, 33.8–2450.5) days. Cumulative mortality was 14.6%, 17.4%, 21.2%, 24.4%, and 33.8% at 1, 2, 3, 5 and 10 years, respectively. The cumulative mortality did not significantly differ by type of stent, and mortality of late ST was higher than that of early ST and very late ST; however, it did not reach statistical significance after the multivariate analysis. Independent predictors of mortality were hemodialysis (hazard ratio [HR], 7.80; 95% CI, 3.07–19.81; P<0.001), culprit lesions in the left main trunk (HR, 8.14; 95% CI, 1.71–38.75; P=0.008), culprit lesions in the left coronary artery (HR, 2.77; 95% CI, 1.10–6.96; P=0.030), and peak creatine kinase (HR, 1.017; 95% CI, 1.011–1.022; P<0.001). Conclusions The 10‐year cumulative mortality after ST reached 33.8%. Close follow‐up is thus mandatory for patients with ST, especially with hemodialysis, culprit lesions in the left main trunk and left coronary artery, and high peak creatine kinase.